Experimental investigation on combustion behaviour, performance and emission of fusel oil-gasoline blends using turbocharged SI engine - S. M., Rosdi; R., Mamat; M. H. M., Yasin; T. F., Yusaf; F., Khoirunnisa (Faculty Mechanical Engineering, UMP, 2022)
Because of rising energy demand and pollution concerns in the transportation and industrial sectors, alternative fuel development is critical. The fusel oil, which is a by-product of ethanol distillation molasses, is receiving a lot of interest. The combustion characteristics, performance, and emissions of a 1.8L turbocharged four-cylinder, port injection, spark-ignition engine will be used to compare fusel oil blends with gasoline in this study. The experiment was carried out at a constant engine speed of 2000 rpm with a throttle load of 10-40%. Four samples with various ratios of gasoline combined with fusel oil were tested (100% gasoline, 10%, 20%, and 30% are referred to as F0, F10, F20, and F30 respectively). As a result, compared to gasoline, fusel oil blends increase Brake Specific Fuel Consumption (BSFC) by 5-22%. In comparison to gasoline, the combustion behaviour of in-cylinder pressure, Rate of Heat Release (ROHR), Rate Of Pressure Rise (ROPR), and Mass Fraction Burn (MFB) shows an early 2-3 Degree Crank Angle (CAD). Due to differences in attributes and oxygen content, the Brake Thermal Efficiency (BTE) of combustion utilising fusel oil blends suffers a modest drop of 13-16%. When compared to gasoline, fusel oil blends emit 3-4% less hydrocarbon (HC), 7.5-24.5% less carbon monoxide (CO), and 18-36% less nitrogen oxide (NOx). To summarise, fusel oil blends without water extraction blended with gasoline have a substantial impact on turbocharger engine functioning.